Clinical and sociodemographic features of alopecia areata in five colombian cities: an analysis of the RENAAC Registry (2024)
Background: Alopecia areata (AA) is an autoimmune disease characterized by non-scaring hair loss and preservation of hair follicles. The information available on disease course, and clinical features of AA is scarce worldwide, and almost nonexistent in Colombia. Objective: To determine the clinical and sociodemographic characteristics of patients diagnosed with AA who presented to a dermatology consultation in five Colombian cities. Material and methods: This was a retrospective and multicenter study on data from an ongoing National Registry of Alopecia Areata in Colombia (RENAAC) collected in Bogota, Cali, Cartagena, Barranquilla, and Medellin, Colombia from March 2022 through April 2023. Data was recorded in a standardized form by trained physicians. The variables were expressed as measures of central tendency and dispersion, and absolute and relative frequencies. Results: A total of 562 patients were included, 59.4% of whom were women, aged between 15 and 49 years (63.9%) with a mean disease course of 1.7 years. The most common finding was multiple plaque (53.2%), the predominant AA subtype was patchy (71.4%), and 29.5% of the patients had a past dermatological history, 18.3% had a past endocrinological history, and 8.9% had a past psychiatric history. The treatments most widely used were steroid injections (76.4%), 5% topical minoxidil (46.4%), followed by high-potency corticosteroids (42.5%). Study limitations and conclusions: AA was slightly predominant in women. As seen in other populations, this disease had an earlier onset in men vs women. Presentation in pediatric age was uncommon. The previous history of other dermatological diseases was checked in almost one third of the patients. Analysis of the co-presentation of AA with other autoimmune diseases is biased due to excluding patients with systemic erythematous lupus from the study.